의약품·의료기기 유통 투명성 제고를 위한 제외국 지출보고 제도 운영 현황: 4개국을 중심으로 - 최연미; Yeonmi Choi; 김병수; Byungsoo Kim; 김유정; Yujeong Kim (HIRA Research, 2023)
The Korea Open Payments will be expanded in June 2023 to strengthen the management of distribution orders for pharmaceuticals and medical devices. This study identified the implications related to the disclosure of payments in Korea through case studies of Open Payments in major foreign countries, including the United States, Japan, France, and Italy, where the government operates Open Payments programs according to their national laws, and suggested operational measures to improve the transparency of the payment. Data were collected by searching the Ministry of Health websites and each country's electronic legal information, and the management systems related to the payments were reviewed. In the United States, the Centers for Medicare and Medicaid Services (CMS) has disclosed the details of payments through the CMS Open Payments web database since the enactment of the Sunshine Act in 2010. However, information disclosure can be withheld for products under research and development, and the recipients have a pre-publication review and dispute period to ensure their data is accurate before the CMS publishes. In Japan, only payments for specific clinical trials are subject to compulsory disclosure under the Clinical Research Act from September 2018, and data collection and disclosure are made on individual company websites. After enacting the law in 2012, France disclosed about 1.39 million payments in 2021. Since 2019, the subject has been expanded to healthcare professionals and health product information providers. Similarly, the law was enacted in Italy in May 2022, and the Ministry of Health operates the web database “Sanit à Trasparente.” Therefore, it is necessary to establish a proper distribution order for pharmaceuticals and medical devices through institutional efforts to enhance the effectiveness, reliability, accessibility, acceptability, and awareness of the Korea Open Payments.